Paragangliomas and Anemia: Literature Review and Case Report - Maria-Daniela Tănăsescu; Ștefan Popescu; Alexandru Mincă; Teodora Isac; Emel Suliman; Maria Mihaela Grigorie; Emine Suliman; Daniel Stăniloaie; Delia Timofte; Dorin Ionescu (Medicina, 2023)
Paragangliomas are rare neuroendocrine tumors that arise from the extra-adrenal autonomic paraganglia, i.e., small organs consisting mainly of neuroendocrine cells that are derived from the embryonic neural crest and have the ability to secrete catecholamines. Paragangliomas can derive from either parasympathetic or sympathetic paraganglia. Most of the parasympathetic ganglia-derived paragangliomas are nonfunctional, and symptoms result from mass effect. Conversely, the sympathetic paragangliomas are functional and produce catecholamine. Although such patients could have symptoms similar to pheochromocytoma, mass effect symptoms, or non-specific symptoms, being benign tumors, they can also present with anemia, specifically iron-deficiency anemia. Considering that neoplastic pathology is chronically accompanied by moderate, normochromic, normocytic anemia, association between paragangliomas that are mostly benign but with a potential degree of malignancy and anemia is not as frequent as expected, with only 12 cases reported in the literature. We report a case of a 54-year-old female patient diagnosed with a paraganglioma of the carotid glomus accompanied by severe normochromic, normocytic anemia, which reached normal limits after excision of the paraganglioma.